Utilization of indonesian megabiodiversity for integrated science learning with nationalism values to develop concepts understanding and soft security among students of border areas - Sukardiyono Sukardiyono; Dadan Rosana (Journal of Science Education Research, 2018)
This research aimed at (1) producing Subject Specific Pedagogic (SSP) of integrated science learning with  nationalism values by utilizing Indonesian megabiodiversity which is valid and practical for the students of border areas, (2) obtaining empirical test results on the effectiveness of SSP integrated science learning with  nationalism values by utilizing Indonesian megabiodiversity to improve the quality of students’ learning outcomes and soft security in border area. The SSP was prepared through a research design referring to  "Prototypal Studies" as put forward by Akker (1999) and Plomp (2001). The important thing that needs to be considered in the development research is the quality of the produced learning tools (product). Plomp (2001) has pointed out the product quality criteria, namely: valid (reflects state-of-the-art knowledge and internal consistency), added value, practical, and effective. This research is intended to solve the problems of junior high schools in the region of (1) Atambua, Belu Regency, East Nusa Tenggara Province, and (2) Entikong, Sanggau Regency, West Kalimantan Province. The reserach results showed that SSP science learning integrating Indonesian megabiodiversity utilization with nationalism values was valid, practical and effective to develop concepts understanding and soft security among students in border areas schools.